Liturgical reform in the "breaking of the bread" in the Lord's Supper in the Palatinate and its resonance in the Heidelberg Catechism - E. de Boer (Acta Theologica)
Liturgical practices mirror the doctrine. Changes in form reflect a changed spirituality. In the reformation of the sixteenth century the practice of the distribution of individual consecrated oblates to the kneeling communicant was replaced in the Palatinate by the breaking of a loaf of bread and the distribution of pieces to the congregation who received it standing or sitting. The present article describes how the reformation was initiated and implemented by the elector Frederic III, what the response from Lutheran theologians was, and how the theological defence from the Heidelberg theologians came to be formulated. The main conclusion of our investigation is that it is not easy to determine which elements in the sacrament – in this case: the Lord’s Supper – are essential or accidental (adiaphoron). While the exegetical basis of a chosen form may be inconclusive, motives behind the choice may be such that exclusion of people from the Christian community is effected or individuality underlined. A healthy view of communality and celebration can undergird the doctrine of the Church and the sacrament.